Stability and trace element composition of natural schwertmannite precipitated from acid mine drainage - Chen, Qian; Cohen, David R.; Andersen, Martin S.; Robertson, Alan M.; Jones, David R. (Applied geochemistry, 2022)
Schwertmannite is an iron hydroxo sulfate secondary mineral (Fe8O8(OH)8-2x(SO4)x•nH2O; 1 ≤ x ≤ 1.75) that commonly precipitates in sulfate-rich acid and metalliferous drainage as Fe(II) oxidises to Fe(III). It displays a high capacity to incorporate a range of elements through substitution of metal cations for Fe and anionic species for inner-sphere and outer-sphere sulfate groups, and surface adsorption. Precipitates from the base to top of sediment profiles immediately downstream from the historic Sunny Corner sulfide deposit are dominated by schwertmannite, indicating the stability of this mineral over decadal time frames in the low pH and high sulfate conditions. Various mineral characterisation methods, coupled with hydroxylamine hydrochloride based sequential selective extractions, reveal two forms of schwertmannite co-existing and in similar proportions throughout the profiles. The first form of schwertmannite has a high S/Fe ratio and the pattern of release of Cu, Pb, Zn and As relative to Fe indicates such trace elements are mostly adsorbed to outer-sphere sites. By contrast, the second and more crystalline schwertmannite has lower S/Fe ratios and requires higher concentrations of hydroxylamine hydrochloride to dissolve. The second schwertmannite displays substantial substitution of arsenate for sulfate, with As/(As + S) molar ratios ranging from 0.1 to 0.6, and substantially higher concentrations of trace elements. Sequential precipitation of the two schwertmannites from the AMD appears more likely than transformation of one form to the other. At sites such as Sunny Corner, pH neutralisation or removal of sulfate from the AMD stream may result in destabilisation of the schwertmannite and release of associated trace metals. [Display omitted] •Schwertmannite stable for decades in sulfate-rich and low pH waters.•Two forms of schwertmannite precipitated in sediments at Sunny Corner mine.•Trace element substitution higher in As-substituted form of schwertmannite.